FORMATION OF ENGINEERING EDUCATION IN RUSSIA AFTER REVOLUTION OF 1917–1945 YEAR - Alexandra Viktorovna Eroshenko (Science and Innovation Center Publishing House, 2020)
The successful development of the economy of any country depends on the quality of education, therefore, one of the priority problems for Russia is to improve the quality of engineering education.